The Development Of Intermodal Transportation In Cirebon - Herry Hermawan (International Conference on Coastal and Delta Areas, 2017)
The progress of a nation is seen from its transportation conditions". This proverb is familiar to us, but it is difficult to realize. The development of technology and information requires a development in the field of transportation. In the context of human movement and goods, a system that regulates its movement to be effective and efficient from origin to destination safely, comfortably, and timely is needed. The term of intermodaltransportation or combined transport system is directed to achieve the effectiveness and efficiency of the movement. Cirebon as a gateway of movement from West Java to Central Java or vice versa is rich in transportation modes. Geographically, its location is strategic with the development of transportation requirementfor air, road and rail modes as well as seaand river transportation modes. The potency of this area is very abundant, ranging from the potency of agriculture, plantation, fishery, tourism and other potential areas that are well known both domestically and internationally. Of course, it requires transportation facilities and infrastructures to support the distribution of the produces. Related to it, the local government has made a transportation planning program that is actually very supportive forthe regional and its potencydevelopment that exist. However, it is needed to have synergy and integration between one transportation mode planning with other modes of transportation due to the limited funds available in local government and central government. It is necessary to develop cooperation between the government and the private sector in realizing the development of intermodal transportation in Cirebon. This paper tries to illustrate the opportunities for the development of intermodal transportation in Cirebon in improving the economy and development of West Java Province, especially Cirebon. The problem discussed here is the long time needed to go to the cities in Central Java (PANTURA track) and also on the existing causeway because of the excessive loads that burden the road, and the condition of damaged roads. In addition, another transportation mode opportunity other than road mode can be an alternative distribution of transportation; thereby it reduces the burden of highway mode. It is expected that the proposed recommendation can be an input for the improvement of transportation system in Cirebon. Keywords: Transportation, Intermodal, Cirebon